Disparities in Current and Future Childhood and Newborn Carrier Identification. Issue 5 (11th July 2014) - Noke, Melissa; Wearden, Alison; Peters, Sarah; Ulph, Fiona
Abstract: International carrier testing guidelines discourage testing in childhood to preserve autonomous decision making and prevent detrimental psychosocial consequences. Despite the discouragement of autosomal recessive carrier testing during childhood, some sickle cell disease (SCD) or cystic fibrosis (CF) carriers are incidentally identified through UK and international newborn screening (NBS). This creates a scenario where parents may have knowledge of their newborn's, but not older child's carrier status. In addition, there is wide variation in the identification of CF and SCD carriers due to the screening technologies implemented by different NBS programs. The current and future availability of childhood testing are determined to some extent by the impact of testing on children and parents (whether this is beneficial or detrimental to wellbeing). However empirical research informing carrier guidance and practice is conflicting. Echoing previous calls, this discussion highlights the need for further qualitative and longitudinal research with children to consider the psychosocial impact of carrier testing on children and role of disclosure from parents on adaptation to results. It is recommended that professionals aim to minimize harms resulting from carrier identification by providing support for parents and children following NBS. Support for non‐genetics specialists from genetic counselors to enable discussion of carrier results with children is suggested.